Penerapan Pajak dan Zakat di Negera Thailand: Taxes and Zakat Practice in Thailand - Nurhakiki; Achmad Nur Alfianto (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
Taxes and zakat are sources of state revenue, both Islamic countries and modern countries. This study aims to determine the management of taxes and zakat in Thailand, which is a country with a minority Muslim population. This research is a qualitative research. The research design uses a literature study approach, the data used is obtained from library sources such as scientific articles, research results, books, and other documents. The results of this study indicate that Thailand, whose population is a Muslim minority, can carry out its religious activities well, including carrying out zakat. The Thai monarchy government provides space for the Muslim population to establish zakat institutions. Most of the practice of zakat in Thailand as in southern Thailand, the management of zakat is centered on mosques and managed by institutions led by Imams or religious experts in the region.